The evolution of flow devices used to reduce flooding by beavers: A review - Jimmy D. Taylor; Russell D. Singleton (Wildlife Society Bulletin)
ABSTRACT Dams created by American beavers (Castor canadensis) are associated with positive and negative values, and beaver management decisions are based on stakeholder perception and levels of tolerance. Lethal trapping is a widely used and accepted tool to reduce beaver damage caused by flooding; however, acceptable and efficacious non‐lethal tools are increasingly desired by the public. We traced the origin of non‐lethal tools used to reduce beaver flooding as far back as the early 20th century, when beavers received protective status and were reintroduced to many areas across North America. These tools focus on 2 general factors—exclusion and deception—and can be categorized as fence systems and pipe systems. We found few technological advances in tools to reduce beaver flooding until the 1980–1990s, when fence systems and pipe systems were integrated to create “flow devices.” There are few studies that evaluate fence systems, pipe systems, and flow devices; however, we address their findings in chronological order. We recommend that natural resource managers avoid using fence systems or pipe systems alone, unless they can be used in areas where maintenance requirements and expected damage are extremely low. Flow devices are not intended to replace lethal control; however, we recommend use of flow devices as part of integrated management plans where beaver flooding conflicts are expected and where local conditions allow flow‐device installation and maintenance. Future research should evaluate flow devices under a range of environmental conditions and include considerations for fish passage. Published 2013. This article is a U.S. Government work and is in the public domain in the USA